Pityriasis lichenoides. A case series highlighting clinical and diagnostic features. - Bawany, F.; Paul, D.; Verhave, B.; Mercurio, M.G.; Scott, G.A.; Cordisco, M.R. (European Journal of Pediatric Dermatology, 2020)
We present 12 patients with variants of Pityriasis Lichenoides (PL), including its chronic form (Pityriasis Lichenoides Chronica, PLC), acute form (Pityriasis Lichenoides et Varioliformis Acuta, PLEVA), and the rare and severe Febrile Ulceronecrotic Mucha-Habermann Disease (FUMHD). As these conditions are commonly misdiagnosed, we highlight common clinical and histopathologic diagnostic features. PLEVA and FUMHD were more clinically severe than PLC, although PLC and PLEVA had several overlapping histopathologic features. Infections or vaccinations preceded half of cases, and one patient had suspected mycosis fungoides, providing insights into the pathophysiology of PL. A variety of treatments were used successfully. This case series offers insights into these conditions that can be challenging to diagnose and treat.